In silico characterisation of minor wave genes and LINE-1s transcriptional dynamics at murine zygotic genome activation - Ansaloni, Federico; Gustincich, Stefano; Sanges, Remo (Frontiers in Cell and Developmental Biology, 2023)
In mouse, the zygotic genome activation (ZGA) is coordinated by MERVL elements, a class of LTR retrotransposons. In addition to MERVL, another class of retrotransposons, LINE-1 elements, recently came under the spotlight as key regulators of murine ZGA. In particular, LINE-1 transcripts seem to be required to switch-off the transcriptional program started by MERVL sequences, suggesting an antagonistic interplay between LINE-1 and MERVL pathways. Here, to better investigate the activities of these elements at ZGA, we integrated publicly available transcriptomics, chromatin accessibility and Pol-II binding datasets and characterise the transcriptional and epigenetic dynamics of MERVL and LINE-1 during murine ZGA. We identified two likely distinct transcriptional activities characterising the murine zygotic genome at ZGA onset. On the one hand, our results confirmed that ZGA minor wave genes are preferentially transcribed from MERVL-rich and gene-dense genomic compartments, such as gene clusters. On the other hand, we identified a set of evolutionary young and likely transcriptionally autonomous LINE-1s located in intergenic and gene-poor regions showing, at the same stage, features such as open chromatin and RNA Pol II binding suggesting them to be, at least, poised for transcription. These results suggest that, across evolution, transcription of two different classes of transposable elements, MERVLs and LINE-1s, have likely been confined in genic and intergenic regions respectively in order to maintain and regulate two successive transcriptional programs at ZGA.